Social class and moral judgment: a process dissociation perspective - Tutic, Andreas; Haiser, Friederike; Krumpal, Ivar (Frontiers in Sociology, 2024)
Do social classes differ in moral judgment? Previous research showed that upper-class actors have a greater inclination toward utilitarian judgments than lower-class actors and that this relationship is mediated by empathic concern. In this paper, we take a closer look at class-based differences in moral judgment and use the psychometric technique of process dissociation to measure utilitarian and deontological decision inclinations as independent and orthogonal concepts. We find that upper-class actors do indeed have a greater inclination toward decisions consistent with utilitarian principles, albeit only to a quite small extent. Class-related differences are more pronounced with respect to deontological judgments, in so far as upper-class actors are less inclined to judgments consistent with deontological principles than lower-class actors. In addition, it is shown that class-based differences in utilitarian judgments are mediated by cognitive styles and not so much by empathic concern or moral identity. None of these potential mediators explains class-based differences in the inclination toward deontological judgments.